Evaluation of the stability of the Caesalpinia spinosa extract under stress-induced conditions. - Guzmán Méndez, Daniela Valentina; Modesti Costa, Geison (Revista Productos Naturales, 2022)
An extract obtained from Caesalpinia Spinosa, has been investigated for several years on the PUJ, because of its therapeutic potential against breast cancer.
Keywords: P2Et; Caesalpinia spinosa; stability; degradation; induced stress